Theory-Based Advanced Nursing Practice: A Practice Update on the Application of Orem's Self-Care Deficit Nursing Theory - Jeffrey Yuk Chiu Yip MNSc, RN (HK) (SAGE Publishing, 2021)
Introduction Many researchers have commended the self-care deficit nursing theory (SCDNT) developed by Orem as a means of improving patients' health outcomes through nurses' contributions. However, experimental research has investigated specific aspects of SCDNT, such as self-care agency and self-care requisites, rather than how the construct is practiced and understood as a whole. The current research presents a case study in which an advanced practice nurse (APN) used SCDNT-led practice within a primary healthcare setting that illustrates how the theory is applied to case management. Methods A case study was conducted by observing an APN during her work in the asthma clinic of a public hospital in Hong Kong. A comparison was made between the case management of the APN under observation with the nursing processes stipulated by the SCDNT across four key operations: diagnostic , prescriptive , treatment or regulatory , and case management . Conclusion During the observed consultation, the APN applied the four key operations. In SCDNT, the role of the APN is to apply practical nursing knowledge by determining how a patient can best undertake self-care within the circumstances of their living arrangements and support facilities. The case study also demonstrated that SCDNT-based nursing practice has strengths and limitations in a primary healthcare setting. The study concluded that Orem's SCDNT serves as an appropriate theoretical framework for nursing practice within primary healthcare settings. One practical consequence of using SCDNT is that it enables APNs to use nurse-sensitive indicators when evaluating their clinical practice. This study offers a practice update to increase the accountability of nursing practice for nurse-led healthcare services.